IN SILICO DOCKING ANALYSIS OF YOHIMBINE ALKALOIDS FROM CATHARANTHUS ROSEUS AGAINST DENGUE FEVER: Insilico Docking Studies - GIRIJA R; ARUNA S; SANGEETHA R (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In this docking study was performed by the active site of NS2B-NS3 protease with selected plant alkaloids derived from Catharanthus roseus. On the basis of docking results, out of the nine alkaloids yohimbine might be considered as the best inhibitors of NS2B-NS3 protease protein. Methods: Lipinski rule was employed to check the ligand likeliness of the compound. The three-dimensional crystallographic structure of NS2B-NS3 protease (ID.2FOM) fetched from the protein data bank. The in silico docking studies were performed by “AutoDock version 4.2” software tool. Results: Yohimbine is having the best binding score (−7.18 Kcal/mol) than the other eight compounds. Conclusion: Hence, it has been concluded yohimbine as a novel inhibitor for NS2B-NS3 protease in dengue fever.